2016
DOI: 10.18006/2016.4(4).427.434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of benzyladenine and salicylic acid on biochemical traits of two cultivars of carnation

Abstract: Plant growth regulators have significant effect on the delaying senescence in buds and flowers. Present study was conducted to find out the effects of Salicylic acid and Benzyl adenine spraying on various biochemical traits such as membrane stability index, chlorophyll a, and b content, total chlorophyll content, sugar content, catalase, and peroxidase enzymes activity, and proline content in Carnation. Study was conducted in a split plot design with three replications and various concentrations of hormones, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Ramtin et al, (2015) reported that BA@50 μM/L increase the floret length and flower diameter in carnation. Ramtin et al, (2016) showed that salicylic acid 100 μM, and benzyl adenine 100 μM had more effects than other plant growth hormones (Table 1).…”
Section: Length Of Upper Bud and Diameter At Spike Harvesting Stage (Mm)mentioning
confidence: 99%
“…Ramtin et al, (2015) reported that BA@50 μM/L increase the floret length and flower diameter in carnation. Ramtin et al, (2016) showed that salicylic acid 100 μM, and benzyl adenine 100 μM had more effects than other plant growth hormones (Table 1).…”
Section: Length Of Upper Bud and Diameter At Spike Harvesting Stage (Mm)mentioning
confidence: 99%
“…Cytokinins (CKs) exert a pivotal influence on various plant processes, such as cell division, stem elongation, reproductive development, and senescence, as well as enhancing environmental stress tolerance (Korobova et al, 2016; Ramtin et al, 2019; Hai et al, 2020; Veselova et al, 2021). Exogenous application of CK delays drought‐triggered senescence, regulates source‐sink alterations and boosts grain yield in rice by modulating CK biosynthesis genes, mainly ISOPENTENYL TRANSFERASE ( IPT ), thereby bestowing drought tolerance (Peleg et al, 2011).…”
Section: Crosstalk Of Ethylene With Other Plant Growth Regulators Und...mentioning
confidence: 99%
“…Also, Ali and Asil (2015) revealed that spraying Schefflera arboricola plants with cytokinins (BA) at 100 mg/l significantly increased photosynthetic pigments contents. Also Youssef and Mady (2013) stated that treating Aspidistra elatior by 75 ppm of BA encouraged the best leaf N, P, K and Ramtin et al (2016) pointed out that the use of foliar spray with a concentration 150 μM of benzyladenine led to an apparent effect and increase in the plant content of chlorophyll (a) and (b) on carnation plants.…”
Section: Chemical Compositionmentioning
confidence: 99%